Formation of Oil-Particle-Aggregates: Numerical Model Formulation and Calibration - Cui, Linlin; Harris, Courtney K.; Tarpley, Danielle R. N. (Frontiers in Marine Science, 2021)
When oil spills occur in turbid waters, the oil droplets and mineral grains can combine to form oil-particle aggregates (OPAs). The formation of OPAs impacts the vertical transport of both the oil and the mineral grains; especially increasing deposition of oil to the seabed. Though the coastal oceans can be very turbid, to date, few numerical ocean models have accounted for aggregation processes that form OPAs. However, interactions between oil and mineral aggregates may be represented using techniques developed to account for sediment aggregation. As part of Consortium for Simulation of Oil Microbial Interactions in the Ocean (CSOMIO), we modified an existing, population dynamics-based sediment flocculation model to develop OPAMOD, a module that accounts for the formation of OPAs. A zero-dimensional model using OPAMOD is shown to be capable of reproducing the size distribution of aggregates from existing laboratory experimental results. Also using the zero-dimensional model, sensitivity tests were performed on two model parameters, the fractal dimension and collision efficiency. Results showed that fractal dimension played a role in the OPA size distribution by influencing the effective particle density, which modified the number concentration of flocs for a given mass concentration. However, the modeled particle characteristics and oil sequestration were relatively insensitive to collision efficiency. To explore OPA formation for an outer continental shelf site, two simulations were conducted using a one-dimensional (vertical) implementation of the model. One scenario had high sediment concentration near the seabed to mimic storm-induced resuspension. The other scenario represented river plume sediment delivery by having high sediment concentration in surface waters. Results showed that OPA formation was sensitive to the vertical distribution of suspended sediment, with the river plume scenario creating more OPA, and sequestering more oil within OPA than the storm resuspension scenario. OPAMOD was developed within the Coupled Ocean-Atmosphere-Wave-and-Sediment Transport (COAWST) modeling system, therefore the methods and parameterizations from this study are transferrable to a three-dimensional coupled oil-sediment-microbial model developed by CSOMIO within the COAWST framework.